Peran Perpustakaan SMPN 85 Jakarta dalam Mendukung Gerakan Literasi Sekolah - Padila, Aldi Rizki; Fauziah, Kiki (UI Scholars Hub, 2023)
This study analyzes the role of the SMPN 85 Jakarta library in supporting the School Literacy Movement. The problem to be discussed in this study is the role of the school library in supporting the school literacy movement. This research aims to identify the school library's role in supporting the School Literacy Movement. This research uses a qualitative approach with a case study method. Data was collected using observation, interviews, and document analysis from August to November 2022. The selection of informants was carried out using a purposive sampling technique. The results of the study show that there is a role for the school library in implementing the School Literacy Movement. The role of the school library in the school literacy movement is that of an innovator and founder. The role of an innovator is to play a role in providing innovation in school literacy movement activities. The resulting innovations are library visit schedules (habitation stage), reading corner competitions (development stage), and reading corners (learning stage). The role of the founder, namely the school library, manages the course of the School Literacy Movement activities from pre-event to post-event.